1999
DOI: 10.1046/j.1365-2672.1999.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of acetic acid treatment and modified atmosphere packaging for extending the shelf-life of chilled chicken breast portions

Abstract: Samples of chicken breasts with skin were treated with a 1% acetic acid solution or untreated and packaged in a 70% CO 2 /30% N 2 modified atmosphere. Two different types of films were studied to establish their usefulness within the above pre-determined conditions. After 3, 7, 14 and 21 d of storage at 4°C, the samples were evaluated for spoilage microbial growth, odour and slime, as well as the gas composition in the headspace volume in the package. As a result of this, it was found that both films were adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…Furthermore, Jiménez et al . [ 31 ] observed that the immersion of chicken breast in a 1% acetic acid solution extended the lag phase of microbial growth.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Jiménez et al . [ 31 ] observed that the immersion of chicken breast in a 1% acetic acid solution extended the lag phase of microbial growth.…”
Section: Resultsmentioning
confidence: 99%
“…To determine Enterobacteriaceae counts (EBC), 1 ml of the appropriate dilution was inoculated by the pourplated method on violet red bile agar (VRBA; Difco Laboratories Inc., Detroit, Michigan, USA) and overlaid with approximately 5 ml of the same growth medium (Jime´nez, Salsi, Tiburzi, Rafaghelli, & Pirovani, 1999), then the plates were incubated at 35 C for 24 h.…”
Section: Enterobacteriaceae Countmentioning
confidence: 99%
“…Enterobacteriaceae counts (EBC), 1 ml of the appropriate dilution was inoculated by the pour-plated method on violet red bile agar (VRBA; Difco Laboratories Inc., Detroit, Michigan, USA) and overlaid with approximately 5 ml of the same growth medium (Jiménez, Salsi, Tiburzi, Rafaghelli, & Pirovani, 1999), then the plates were incubated at 35°C for 24 h.…”
Section: Enterobacteriaceae Count-to Determinementioning
confidence: 99%